ENGAGING STUDENT TEACHERS IN HYBRID COLLABORATIVE WRITING CLASS - indriani, lilia; Estiyowati Ikaningrum, Rini (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
Google docs is widely researched for its effect on students’ writing accuracy, however, previous studies have not discussed its effects on student teachers’ achievement and the engagement in hybrid collaborative writing class. The purpose of this study is to fill the gaps. Fifty English study program student teachers at a university in Indonesia are the subjects. Twenty-five student teachers from the experimental group did collaborative writing activity by using google docs in their process of writing whereas the rest as the control group did individual writing although for idea development, they worked together by using WhatsApp. Data collection was from pretests, posttests and from questionnaires. The study reveals that hybrid collaborative writing enhances student teachers’ engagement and has a great effect on students’ teacher writing achievement in hybrid learning class.